TINDAK TUTUR EKSPRESIF DALAM KOMENTAR WARGANET DI INSTAGRAM @KOMPASCOM TENTANG ISU TAMBANG NIKEL DI RAJA AMPAT - Siti Kurniasih; Ilmi Solihat; Robita Ika Annisa (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This research intends to outline the various forms and roles of expressive speech acts observed in comments from internet users on Instagram concerning the nickel mining situation in Raja Ampat. The study employs a qualitative approach, gathering data from comments on an Instagram post shared by @kompascom. Data collection was carried out through methods of observation, note-taking, and documentation. The research results show 66 data with five types of expressive speech acts, namely sarcasm, anger, criticism, concern, and hope.The results suggest that social media acts as a platform for individuals to communicate their emotional responses, critiques, and concerns about environmental matters. Additionally, the outcomes of this research can be utilized in teaching the Indonesian language, especially in argumentative writing lessons for Grade XI Phase F within the Merdeka Curriculum.